Back Matter Jurnal Litbang Industri Vol. 12 No. 1 Juni Tahun 2022 - Sofyan Sofyan (Institution for Industrial Research and Standardization of Industry - Padang, 2022)
Back Matter Jurnal Litbang Industri Vol. 12 No. 1 Juni Tahun 2022